Liver-derived exosome-laden lncRNA MT1DP aggravates cadmium-induced nephrotoxicity. (March 2020) - Gao, Ming; Dong, Zheng; Sun, Jinfang; Liu, Wei; Xu, Ming; Li, Changying; Zhu, Pan; Yang, Xingfeng; Shang, Xiaohong; Wu, Yongning; Liu, Sijin
Abstract: Cadmium (Cd) is a well-characterized toxic heavy metal which could cause severe kidney injury. However, currently the knowledge of Cd toxicity towards kidney is still insufficient. Our previous data has identified that MT1DP (metallothionein 1D pseudogene) could promote Cd-induced detrimental effects on hepatocytes. Herein, we further found that MT1DP was also an important intermediate to aggravate Cd-induced nephrotoxicity. Through analyzing the data of 100 residents from Cd-contaminated area in Southern China, we found that the blood MT1DP levels correlated to the urine Cd content and the extent of nephrotoxicity. Although MT1DP was predominantly induced by hepatocytes in the liver, liver-secreted MT1DP was found to be packaged into extracellular cargoes: exosomes, by which MT1DP was delivered into circulation and thereafter targeted kidney cells. Furthermore, exosome-laden MT1DP worsened Cd-induced nephrotoxicity, as evidenced in both Cd-poisoned individuals and in vitro cells. Moreover, MT1DP was found to reinforce Cd-induced toxicity in kidney cells by indirectly breaking the equilibrium between the pro-apoptotic and anti-apoptotic effects conducted by BAX and Bcl-xL, respectively. Collectively, our data unveiled that hepatocyte-derived MT1DP depends on the delivery of exosomes to wreak considerable havoc in Cd nephrotoxicity. This study offers new insights into the molecular mechanisms of Cd-induced kidney injury. Graphical abstract: LncRNA MT1DP was quickly and significantly induced by Cd treatment in the liver, and then MT1DP was packed into exosomes and sorted into the extracellular space; liver cell-secreted exosomes were recognized and taken up by kidney cells where MT1DP released from exosomes and promoted Cd-induced kidney cell death through regulating the protein levels of BAX and Bcl-xL. Image 1 Highlights: Exosome-laden lncRNA MT1DP aggravate Cd-induced nephrotoxicity. Liver-derived MT1DP could be packaged into exosome and then uptaken by the kidney. BAX and Bcl-xL protein are the toxic effectors of exosomal MT1DP in the kidney. Abstract : Liver-derived exsomal lncRNA MT1DP is correlated to the urine Cd content and the extent of nephrotoxicity, which could promote Cd-induced kidney cells injury.